Facilitation Technologies in the Process of Understanding of the Writerâ€™s Biography - Ivanovna Grakhova, Svetlana; Anatolievna Okisheva, Karina; Mikhailovna Zakharova, Irina; Viktorovna Potanina, Aleksandra (International Journal of Engineering and Technology, 2018)
The article presents the methodology of organizing educational activities to study a writerâ€™s biography with the help of facilitation approach. A key aspect of the paper is the group work model, i.e., â€œThe World CafÃ©â€ which allowed the authors to process and comprehend a large amount of information about F.M. Dostoevsky, share it with students, and plan further work on the study of his creative writing.In addition, the article identifies important concepts in the comprehension of the first part of the posthumous biography â€œThe materials for the biography of F.M. Dostoevskyâ€. The compiler of the biography was O.F. Miller, a professor of literature in St. Petersburg University (Russia), critic, publicist, and a famous educator of the 19th century. Interestingly, â€œMaterials for the biography of F.M. Dostoevskyâ€, published in 1883, were not fully republished and did not receive sufficient scientific understanding until 2010, even though the work of O.F. Miller remained the main source the experts studying F.M. Dostoevsky. Of much importance is the fact that some parts of â€œMaterials for the biography of F.M. Dostoevskyâ€ appeared on the Internet only after 2012. This paradox highlights the importance of the research describing the biography.Â  In 2010, the personal history â€œMaterials for the biography of F.M. Dostoevskyâ€ became an integral part of the academic thesis by K.A. Okisheva â€œF.M. Dostoevsky and O.F. Miller: the history of relationshipsâ€. Our present study highlights the importance of biographies for the education of young generations. Our major concern is the methodology, according to which personal historyâ€™s information serves as an essential part of roundtable discussions which simultaneously target the acquisition of F.M. Dostoevskyâ€™s biography and innovative classroom activities.Â